2021
DOI: 10.1161/hypertensionaha.121.17702
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Diameter and Arterial Stiffness: Conjoint Relations to the Incidence of Cardiovascular Disease in the Framingham Heart Study

Abstract: Higher central pulse pressure is associated with higher carotid-femoral pulse wave velocity (CFPWV) and an increased risk of cardiovascular disease (CVD). A smaller aortic root diameter (AoR) is associated with higher central pulse pressure. We hypothesized that the combination of a smaller AoR and higher CFPWV is associated with increased CVD risk (relative to a larger AoR and lower CFPWV). We tested this hypothesis in the community-based Framingham Study (N=1970, mean age 60 years, 57% women). We created sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Several reports have suggested that the enlargement of the arterial lumen diameter might compensate for age-related increases in arterial stiffness and help preserve the buffering capacity of the central artery. However, this compensatory mechanism could be maladaptive, ultimately leading to a poorer prognosis [ 7 , 20 , 21 ]. This concept could potentially explain the discrepancy between the negative correlation of ARD/BSA with pWAB and the positive association of ARD/BSA with all-cause mortality and MACE observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the enlargement of the arterial lumen diameter might compensate for age-related increases in arterial stiffness and help preserve the buffering capacity of the central artery. However, this compensatory mechanism could be maladaptive, ultimately leading to a poorer prognosis [ 7 , 20 , 21 ]. This concept could potentially explain the discrepancy between the negative correlation of ARD/BSA with pWAB and the positive association of ARD/BSA with all-cause mortality and MACE observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its conduit function, the aorta provides a cushioning function via its compliance, allowing for the near steady flow in the systemic microvasculature despite the intermittent left ventricular ejection. Aortic structural parameters (including geometry and wall stiffness) have been shown to be key determinants of pulsatile arterial hemodynamics 1,2 . A stiff aorta loses its cushioning function, resulting in excess arterial pulsatility and damage to the systemic microvasculature of target organs.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, a stiff aorta increases pulsatile left ventricular afterload, contributing to the pathogenesis of left ventricular hypertrophy and heart failure. Multiple studies have shown that aortic stiffness is a key determinant of pulse pressure, is involved in the pathogenesis of isolated systolic hypertension, and independently predicts the risk of incident cardiovascular events 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Interestingly, the aortic diameter was found to be inversely associated with PP. [7,9] The above findings seem to be contradictory. In a study, Vasan, et al [10] proposed that aortic dilatation might compensate for impaired aortic compliance by increasing the local storage capacity of blood during systole.…”
mentioning
confidence: 98%